Sharia Governance Analysis on Microfinance Arrum BPKB at Branch Pegadaian Syariah Blauran Surabaya City - Warang, Japri Yusrifal; Mustofa, Mustofa; Ritonga, Iskandar (Perisai : Islamic Banking and Finance Journal, 2024)
This study tried to see (1). How the Pegadaian Syariah Branch Blauran Surabaya City conductsmicrofinancing Arrum BPKB. (2). How the Sharia Pegadaian Branch Blauran Surabaya City implements Sharia Governance in Arrum BPKB microfinancing . This type of research combines qualitative methodology with field research. Interviews, observations, recordings, note-taking, and documentation are used to collect data. The informants in this study are leaders, micro staff and microfinance customers. The research findings show, (1). The practiceof microfinancing Arrum BPKB at Pegadaian Syariah Branch Blauran is line with guidelines fatwa number 25/DSN-MUI/III/2002 concerning Rahn, and fatwa nomor 68/DSN-MUI/III/2008 concerning Rahn Tasjily. Meanwhile, microfinance using Arrum BPKB is carried out using two contracts, namely: the Rahn contract as a contract to hold marhun and Ijarah as a contract to obtain rental fees for marhun savings services. There are three mechanisms in financing Arrum BPKB including, a. Stages of applying for financing, b. Stages of financing decisions, c. Stages after financing. (2) . Arrum BPKB at Pegadaian Syariah Branch Blauran financing starts from the stages of applying for financing, financing decisions and after financing there is conformity with Sharia Governance which consists of five principles, namely: the principle of transparency, the principle of accountability, the principle of responsibility, the principle of independence and the principle of justice. Keywords: Sharia governance, Microfinance, Arrum BPKB, and Sharia Pawnshop.